Boron neutron capture therapy (BNCT) as a new approach for clear cell sarcoma (CCS) treatment: Trial using a lung metastasis model of CCS. (December 2015) - Andoh, Tooru; Fujimoto, Takuya; Suzuki, Minoru; Sudo, Tamotsu; Sakurai, Yoshinori; Tanaka, Hiroki; Fujita, Ikuo; Fukase, Naomasa; Moritake, Hiroshi; Sugimoto, Tohru; Sakuma, Toshiko; Sasai, Hiroshi; et al.
Abstract: Clear cell sarcoma (CCS) is a rare malignant tumor with a poor prognosis. In the present study, we established a lung metastasis animal model of CCS and investigated the therapeutic effect of boron neutron capture therapy (BNCT) using p -borono-l -phenylalanine (l -BPA). Biodistribution data revealed tumor-selective accumulation of 10 B. Unlike conventional gamma-ray irradiation, BNCT significantly suppressed tumor growth without damaging normal tissues, suggesting that it may be a potential new therapeutic option to treat CCS lung metastases. Highlights: BNCT trial was performed on a newly established lung metastasis model of clear cell sarcoma (CCS). A significant decrease of the tumor-volume was seen by single BNCT with the use ofl -BPA. BNCT can be a promising therapeutic option for the lung metastasis of CCS.